UMBILICAL HERNIA: DISEASE MECHANISM, DIAGNOSIS AND TREATMENT OPTIONS – A REVIEW OF THE LITERATURE - Wiktor Tracz,; Konrad Strużek,; Kinga Teper,; Aleksandra Anna Strzelecka,; Patrycja Świercz,; Aleksandra Ewa Basak,; Agnieszka Kwiatkowska,; Ewelina Mączka,; Sandra Khiralla-Gawlik, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Umbilical hernia (UH) is a common abdominal wall defect characterized by the protrusion of abdominal contents through the umbilical ring. UH accounts for 6–14% of adult abdominal wall hernias, with higher prevalence in specific populations such as obese individuals and those with ascites. Untreated UH can lead to complications like incarceration or strangulation. Clinical symptoms include a palpable bulge (90–100%), discomfort (50–70%), and pain (20–40%). Diagnosis is primarily clinical, supplemented by imaging in complex cases.Objective: This review aim is to discuss current literature on UH, focusing on its epidemiology, clinical presentation, diagnostic approaches and treatment options, with an emphasis on various methods of surgical treatment, their possible effectiveness and when non-surgical management  is advised.Treatment: Surgical treatments, including mesh and suture repairs via open or laparoscopic approaches, are the mainstay, with mesh repairs showing lower recurrence rates (2–8%) compared to suture repairs (6–54%). Laparoscopic techniques offer reduced postoperative complications for larger hernias. Non-surgical management, such as watchful waiting, is limited but may be suitable for small, asymptomatic hernias.Conclusion: Mesh-based surgery, particularly laparoscopic, are preferred for most umbilical hernia cases due to lower recurrence rates, though treatment should be individually tailored to patient and hernia characteristics.